2021
DOI: 10.1001/jamahealthforum.2021.0456
|View full text |Cite
|
Sign up to set email alerts
|

Association of eConsult Implementation With Access to Specialist Care in a Large Urban Safety-Net System

Abstract: IMPORTANCE Accessing specialty care continues to be a persistent problem for patients who use safety-net health systems. To address this access barrier, hospital systems have begun to implement electronic referral systems using eConsults, which allow clinicians to submit referral requests to specialty clinics electronically and enable specialty reviewers to resolve referrals, if appropriate, through electronic dialogue without an in-person visit.OBJECTIVE Measure the effect of implementing an eConsult program … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…For example, many federally qualified health centers (such as county or regional health systems) are paid by capitation and are often supply constrained. Studies have shown that county and city health systems, which predominantly serve Medicaid patients, can suffer from long wait times (Barnett et al., 2017; Gaye et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, many federally qualified health centers (such as county or regional health systems) are paid by capitation and are often supply constrained. Studies have shown that county and city health systems, which predominantly serve Medicaid patients, can suffer from long wait times (Barnett et al., 2017; Gaye et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Access issues are exacerbated in supply‐constrained systems, such as public healthcare delivery systems. For example, many Medicaid programs and federally qualified health centers have implemented policies to address these concerns (Barnett et al., 2017; Gaye et al., 2021; Rosenbaum et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Electronic consultation has become more widespread in recent years, extending the benefits of the consultation process. 1 , 2 , 3 Consultation in anatomic pathology is an important component of the quality assurance functions in a laboratory and can prevent misdiagnosis. Prior studies in our department, as well as in many others, have shown significant numbers of major diagnostic discrepancies on re-review of pathology reports from other institutions’ pathology departments.…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical setting, the availability of such consultation has decreased patient waiting times for specialist consultation and has had a particularly positive effect in patient populations that are underserved. 1 , 2 Surgical specialties have noted increased efficiency in scheduling surgical intervention in their waiting lists when utilizing e-consultation. 3 …”
Section: Introductionmentioning
confidence: 99%
“…The BASE eConsult model has been spread and scaled up in several other Canadian jurisdictions [ 7 ] and has demonstrated effectiveness in reducing wait times, achieving high levels of patient and provider satisfaction, and lowering costs of care [ 8 11 ]. A review of similar international eConsultation models has shown similar benefits [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%